Assessment of the impact of post-injection on exhaust pollutants emitted from a diesel engine fueled with biodiesel. (December 2017) - Li, Hao; Song, Chonglin; Lv, Gang; Pang, Huating; Qiao, Yuehan
Abstract: This paper reports the effect of post-injection on pollutant emissions from a four-cylinder, direct-injection diesel engine fueled with biodiesel. Characteristics of exhaust pollutants were measured and evaluated for different main-post intervals (MPIs) and post-injection rates (PIRs). Measurements included emissions of carbon monoxide (CO), total hydrocarbons (THC), nitrogen oxides (NOx ) and particulate matter (PM), the particle number concentration distribution, and the reactivity and graphitization degree of the soot particles. Increasing the MPI or PIR increased the emissions of CO and THC but decreased those of NOx . At both low and high MPI values, higher PM emissions and particle number concentrations were observed for the 12 and 20% PIRs. At a PIR of 4%, PM emissions and particle number concentration increased with the increase in MPI. The size distributions of exhaust particulates exhibited a trimodal character under the applied operating conditions. The particle geometric mean diameter decreased with the increase in MPI, probably as a result of an increased yield of soluble organic compounds. Post-injection significantly impacted the reactivity of emitted soot particles, as evidenced by changes in the graphitization degree of soot. Highlights: Pollutant characteristics were measured under different MPI and PIR conditions. Increasing MPI or PIR increased CO and THC emissions but decreased NOx. Close and far post injections increased particle number and mass for high PIR. Increasing MPI increased the particle number and mass for small PIR. Applying post injection affected soot reactivity and its graphitization degree.